Influence of Solvent Polarity and DNA-Binding on Spectral Properties of Quaternary Benzo[c]phenanthridine Alkaloids - Rájecký, Michal; Šebrlová, Kristýna; Mravec, Filip; Táborský, Petr (PLOS ONE, 2015)
Quaternary benzo[c]phenanthridine alkaloids are secondary metabolites of the plant families Papaveraceae, Rutaceae, and Ranunculaceae with anti-inflammatory, antifungal, antimicrobial and anticancer activities. Their spectral changes induced by the environment could be used to understand their interaction with biomolecules as well as for analytical purposes. Spectral shifts, quantum yield and changes in lifetime are presented for the free form of alkaloids in solvents of different polarity and for alkaloids bound to DNA. Quantum yields range from 0.098 to 0.345 for the alkanolamine form and are below 0.033 for the iminium form. Rise of fluorescence lifetimes (from 2–5 ns to 3–10 ns) and fluorescence intensity are observed after binding of the iminium form to the DNA for most studied alkaloids. The alkanolamine form does not bind to DNA. Acid-base equilibrium constant of macarpine is determined to be 8.2–8.3. Macarpine is found to have the highest increase of fluorescence upon DNA binding, even under unfavourable pH conditions. This is probably a result of its unique methoxy substitution at C12 a characteristic not shared with other studied alkaloids. Association constant for macarpine-DNA interaction is 700000 M-1.